Health Behavior of Adolescent Smokers During Covid-19 Pandemic - Helina, Muria; Jayaputra, Novi Hendrika; Palutturi, Sukri (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This research aims to determine the health behavior of adolescent smokers during the COVID-19 pandemic. METHOD: Both quantitative and qualitative analyses were conducted simultaneously using the design of “t” and Chi-square test through the distribution of questionnaires to 135 respondents as well as descriptive design and case studies, respectively. The data were collected by 13 informants through in-depth interviews, observation, and documentation. RESULTS: The results showed that 5 out of the 6 indicators of the demographic characteristics were correlated to the economic pressure of the families of adolescent smokers which also correlates with their health behavior during the COVID-19 pandemic. CONCLUSION: The increase in the price of cigarettes and family control are measures that regulate children from buying cigarettes.